A formação do leitor : mediadores de leitura dos filhos de cortadores de cana da região de Umuarama-PR - Lopes, Sonia Maria Rodrigues (2006)
It is almost an idiom to talk about reading, or its lack, as if it were the redeemer of every situation which concerns education. Incentive campaigns for reading have been implemented with the objective of reducing the pessimistic conclusions pointed at national and international researches about it. The most modern ones affirm that we live at an age in which we read more, although we do it by computer. It is observed, however, that reading, or its lack concerns to other questions one of them is the existence of populations which seem have not got to the "Book Age", when many are already talking about "Digital Age". Considering reading as practice, subject to variants (social, family, school and personal), based on theoretical presuppositions of the Reading Sociology, our objective is to research the reading mediators for this clientele observing the reading conceptions, literature and reader of the children of the cane fields workers from the regions of Umuarama - PR, as well as the ones postulated by coordinators and teachers of the school in which these clientele studies. Thus, based on ethnographic research, we observe how this group develops its reading practice. We limited a selection of the children to three requirements: being children of cane cutters, studying in elementary school from first to fourth grades at the same school. Questionnaires and interviews were applied, firstly to parents, teachers and pedagogical staff and afterwards to the children. The reasearch was defined to a city where the parents live, of which they commute to work up to nearby regions until 60 kilometers farther. We verified that the researched children go to school in the morning and, in the afternoon they are assisted by the projects II Time (Second time) and PETI (Program of Eradication of the Infantile Work). Parents, children and teachers have the reading conception as something really important because it brings information and knowledge. The interests for hearing stories pre nearby vails in the group because these children come from families brought up prioritizing the spoken language. Although they say they like stories, few of them read, but all of them know traditional tales because they hear, from their families, popular and folkloric stories and tales. The school, at the speech of the teachers, has few places for the reading practice. For the teachers, the children "must read" and justify their speech with jargons of advertisements of the government which motivate reading. Reading, taken as practice, reveals its precarious situation in the social, family and school contexts. As they do not have reading of literary texts at the social and family group, the responsibility of the reading formation is given to school, which at the pedagogical staff speech, is responsibility of the teachers. Therefore, it is obligation of these professionals to make this clientele, who is formed only at spoken language but appreciates popular reading and knows traditional tales; readers of literary texts. To understand the importance of the spoken literature, for that group, is a very important aim to the mediators of reading at the school context.